2018
DOI: 10.1017/s0031182018001737
|View full text |Cite
|
Sign up to set email alerts
|

Hexokinase as a versatile molecular genetic marker for Microsporidia

Abstract: Hexokinase (HK) is a core glycolytic enzyme of Microsporidia which regulates host cell metabolic processes. The goal of the present study was to test for the utility of HK for molecular phylogenetics, species identification and molecular detection of microsporidia in infected insects. HK sequence-based reconstructions were essentially similar to those based upon largest subunit RNA polymerase (RPB1) gene sequences, as well as previously published rRNA gene and genome-based trees. Comparing HK sequences allowed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The microsporidium used for the purposes of the present study showed 100% sequence identity to the respective Genbank record # MH669406 corresponding to N. pyrausta hexokinase (Tokarev et al, 2019). This verifies the diagnosis of the parasite as N. pyrausta.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…The microsporidium used for the purposes of the present study showed 100% sequence identity to the respective Genbank record # MH669406 corresponding to N. pyrausta hexokinase (Tokarev et al, 2019). This verifies the diagnosis of the parasite as N. pyrausta.…”
Section: Resultssupporting
confidence: 73%
“…This "natural" isolate was propagated in O. furnacalis laboratory culture using alimentary infection of 2 nd -3 rd instar larvae followed by spore isolation from fully-grown larvae and pupae (Grushevaya et al, 2018). Prior to further experiments, a spore aliquot was used for DNA extraction and PCR using NbHKfor1 and NpyrHKrev1 primers specific to N. pyrausta hexokinase (Tokarev et al, 2019) to confirm the species diagnosis. Total DNA was extracted using a simplified protocol of Sambrook et al (1989) without addition of phenol, with adjustments in the volumes of DNA washing agents .…”
Section: Microsporidium Source Rearing and Identificationmentioning
confidence: 99%
“…The PCR products were directly sequenced using an ABI Prism Genetic Analyzer 3500 (Applied Biosystems, Waltham, MA, USA). Alternatively, the N. pyrausta- specific NpyrHKfor1:NbHKrev1 primers were used for direct PCR detection of the pathogen [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…For DNA analysis, genomic DNA was extracted routinely (Malysh et al., 2019) from spore samples, infected larvae, and experimental egg batches, followed by PCR and amplicon sequencing with 18f:1047r flanking a ca. 850 bp long region of microsporidia small subunit ribosomal RNA (SSU rRNA) gene (Weiss & Vossbrinck, 1999) and NbHKfor1:NpyrHKrev1 primers flanking a 709 bp long region of N. pyrausta hexokinase (Tokarev et al., 2019). For gene expression analysis, total RNA was extracted using ‘Trizol reagent’ and deoxyribonuclease I (both Thermo Fisher Scientific, Waltham, MA, USA), cDNA was synthesized using RevertAid reverse transcriptase and Oligo(dT)18 primer (Thermo Fisher), and PCR was run using primers NpyrHKfor1:NbHKrev1 flanking a 175 bp long region of N. pyrausta hexokinase (Tokarev et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…850 bp long region of microsporidia small subunit ribosomal RNA (SSU rRNA) gene (Weiss & Vossbrinck, 1999) and NbHKfor1:NpyrHKrev1 primers flanking a 709 bp long region of N. pyrausta hexokinase (Tokarev et al., 2019). For gene expression analysis, total RNA was extracted using ‘Trizol reagent’ and deoxyribonuclease I (both Thermo Fisher Scientific, Waltham, MA, USA), cDNA was synthesized using RevertAid reverse transcriptase and Oligo(dT)18 primer (Thermo Fisher), and PCR was run using primers NpyrHKfor1:NbHKrev1 flanking a 175 bp long region of N. pyrausta hexokinase (Tokarev et al., 2019). Quantitative data of microsporidian prevalence levels were analyzed using Fisher’s exact test (Fisher, 1954).…”
Section: Methodsmentioning
confidence: 99%